2014
DOI: 10.1172/jci78272
|View full text |Cite
|
Sign up to set email alerts
|

Hair keratin mutations in tooth enamel increase dental decay risk

Abstract: B r i e f r e p o r t5hair in the facial area upon shaving, is associated with a polymorphism (rs2232387) in the KRT75 gene and more prevalent in AfricanAmericans due to the curly nature of their hair (23). This G-to-A missense mutation (KRT75 GA or KRT75 AA genotypes) leads to an alanine-to-threonine substitution at position 161 (A161T) in a highly conserved region of the 1A α-helical segment of KRT75 ( Figure 1E). To determine whether the KRT75 A161T mutation had clinical impact on enamel function, we tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 31 publications
6
44
0
3
Order By: Relevance
“…Some papers focused on SNP in 1 gene, others on SNPs in several genes. In the majority of the quoted researches caries was evaluated using the DMFT/DMFS index for permanent dentition and the dmft/dmfs index for primary dentition, excepting Duverger et al [2014] (caries presence/absence), Fine et al [2013] (X-ray evaluation), and Fushan et al [2009] (no caries evaluation). The age range of the patients was from 1 to 84 years (9 studies considered children, 9 adults, and 11 both children and adults).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers focused on SNP in 1 gene, others on SNPs in several genes. In the majority of the quoted researches caries was evaluated using the DMFT/DMFS index for permanent dentition and the dmft/dmfs index for primary dentition, excepting Duverger et al [2014] (caries presence/absence), Fine et al [2013] (X-ray evaluation), and Fushan et al [2009] (no caries evaluation). The age range of the patients was from 1 to 84 years (9 studies considered children, 9 adults, and 11 both children and adults).…”
Section: Resultsmentioning
confidence: 99%
“…Authors of some studies included in the review observed the SNP phenomenon in genes involved in amelogenesis [Slayton et al, 2005;Deeley et al, 2008;Patir et al, 2008Kang et al, 2011;Olszowski et al, 2012;Shimizu et al, 2012;Tannure et al, 2012a, b;Wang et al, 2012b;Gasse et al, 2013;Chaussain et al, 2014;Duverger et al 2014;Abbasoğlu et al, 2015;Anjomshoaa et al, 2015;Shaffer et al, 2015;Yildiz et al, 2016]. Amelogenesis is a genetically controlled process of enamel development.…”
Section: Discussionmentioning
confidence: 99%
“…Ces deux symptomatologies démontrent clairement la fonction cruciale de la kératine 75 dans la gaine de soutien entourant le poil, assurant son guidage au cours de sa croissance ainsi que son ancrage dans la peau. Grâce à une collaboration avec les départements de génétique et d'odontologie de l'université de Pittsburgh (Pennsylvanie, États-Unis), permettant d'associer données génétiques et examens intra-oraux dans une large population d'adultes et d'enfants, nous avons montré que ces deux polymorphismes dans la kératine 75 étaient également associés à un risque plus élevé de développer des caries dentaires [3]. aussi des facteurs génétiques affectant la structure de l'émail ou la composition de la salive [10].…”
Section: Mutations Dans Les Kératines Du Poil Et Risque De Cariesunclassified
“…Le développement des caries fait intervenir de nombreux facteurs tels que l'alimentation, le mode de vie, l'hygiène, mais Fonction des kératines du poil dans l'émail dentaire En analysant de près l'émail de patients porteurs du polymorphisme associé à la pseudo folliculite de la barbe, nous avons démontré que la mutation dans la kératine 75 rend la gaine des prismes de l'émail instable, affecte l'arrangement des prismes, est associée à une réduction de la dureté de la couche interne de l'émail, et favorise la formation de lésions carieuses tubulaires [3]. De façon similaire à sa fonction dans le follicule pileux, la kératine 75 semble donc jouer un rôle crucial dans le guidage des prismes de l'émail au cours de leur formation ainsi que dans le maintien de leur cohésion dans l'émail mature.…”
Section: Impact Médicalunclassified
See 1 more Smart Citation